1997
DOI: 10.1165/ajrcmb.17.1.2781
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophages in Sarcoidosis Coexpress High Levels of CD86 (B7.2), CD40, and CD30L

Abstract: Alveolar macrophages (AM) from sarcoid patients have been shown to be good antigen presenting cells (APC) unlike normal AM which are usually ineffective. We demonstrate in ten consecutive sarcoid patients that most of their AM, unlike normal AM, do coexpress high levels of CD86, CD40, and CD30L, all known to be important for T-cell activation. CD80 is also slightly more expressed on sarcoid AM than on normal AM, but is detected on only 26 +/- 6% (mean +/- SEM) of sarcoid AM. A good correlation is present betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…With regard to IL-12 production in APCs, not only LPS stimulation but also the interaction between CD40 and CD40 ligand are important (33). Significantly enhanced expression of CD40 was observed in alveolar macrophages of sarcoid cases compared with that in normal alveolar macrophages (34). The interaction of CD40 and CD40 ligand may be a clue to the greater induction of IL-12 p70 in sarcoid BAL fluid cells than in normal BAL fluid cells.…”
Section: Discussionmentioning
confidence: 98%
“…With regard to IL-12 production in APCs, not only LPS stimulation but also the interaction between CD40 and CD40 ligand are important (33). Significantly enhanced expression of CD40 was observed in alveolar macrophages of sarcoid cases compared with that in normal alveolar macrophages (34). The interaction of CD40 and CD40 ligand may be a clue to the greater induction of IL-12 p70 in sarcoid BAL fluid cells than in normal BAL fluid cells.…”
Section: Discussionmentioning
confidence: 98%
“…Our data are supported by several reports. Cells isolated by BAL from human patients with inflammatory lung disease that were cytologically classified as alveolar macrophages have been shown to function similar to DCs because the cells were capable of inducing T cell responses (28,29). Inflammatory stimuli have been shown to induce activation of alveolar macrophages (38,39) in mice and inhibit their immunosuppressive activity (30).…”
Section: Discussionmentioning
confidence: 99%
“…In two studies using AM isolated by BAL and evaluated by flow cytometry, normal AM were reported to be B7-1 ¹ and weakly positive for B7-2, and the expression of these costimulatory molecules was not increased by culture in the presence of IFN-g [14,15]. From these results, the authors suggested that the poor ability of AM to serve as accessory cells for antigen-induced T cell proliferation is due to defective expression of B7 molecules.…”
Section: Discussionmentioning
confidence: 99%